2014
DOI: 10.1186/s12935-014-0122-8
|View full text |Cite
|
Sign up to set email alerts
|

Nucleofection optimization and in vitro anti-tumourigenic effect of TRAIL-expressing human adipose-derived mesenchymal stromal cells

Abstract: BackgroundTumour homing capacity of engineered human adipose-derived mesenchymal stromal cells (ADMSCs) expressing anti-tumour agents might be the key for a much safer and yet efficient targeted tumour therapy. However, ADMSCs exhibit resistant to most gene transfection techniques and the use of highly efficient viral vectors has several disadvantages primarily concerning safety risk. Here, we optimized the use of highly efficient and safe nucleofection-based transfection using plasmid encoded for TNF-Related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Afterwards, we investigated the mechanism underlying this cell death by checking the expression of TRAIL and Noxa recognized to be involved in the extrinsic and intrinsic apoptotic pathways respectively. MSCs are not known to express TRAIL but are considered as promising tool in cancer therapy when transfected with TRAIL-encoded plasmid 39 , 40 . We observed that RLR activation in MSCs induced the expression of TRAIL mRNA and that expression was ligand dose and MSC-type dependent, whit the highest expression observed in WJ-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards, we investigated the mechanism underlying this cell death by checking the expression of TRAIL and Noxa recognized to be involved in the extrinsic and intrinsic apoptotic pathways respectively. MSCs are not known to express TRAIL but are considered as promising tool in cancer therapy when transfected with TRAIL-encoded plasmid 39 , 40 . We observed that RLR activation in MSCs induced the expression of TRAIL mRNA and that expression was ligand dose and MSC-type dependent, whit the highest expression observed in WJ-MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cytogenetic stability of MSCs following viral transduction needs to be established to the allay safety issues of malignant transformation. The nucleofection technology is a safe non-viral electroporation-based transfection system (24,25). In this study, we modified ADSCs with the plasmid pcDNA3.1 that can expressed the OX40Ig fusion protein in eukaryotic expressiion systems by nucleofection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have used an approach related to the enhancement of certain properties of MSCs; for example, the tumor tropism of MSCs by inducing the over expression of CXCR1 or pre‐exposure of MSCs to soluble factors . In addition, improving the MSC properties is achieved by increasing the transfection effectiveness of MSCs . An alternative approach is to use modified MSCs in combination with other anticancer agents, which allows more effective therapy.…”
Section: Discussionmentioning
confidence: 99%